1980
DOI: 10.1007/bf00261207
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of quantitating 99mTc-EHDP uptake in sacroiliac scintigraphy

Abstract: Quantitative sacroiliac (SI) scintigraphy was performed 3 h after an i.v. injection of 16 mCi 99mTc-EHDP. The resulting images were recorded and processed and on an ON data system 150. Five technical approaches for objective digital assessment of abnormal uptake of the tracer at the sacroiliac joints were employed. SI indexes from the ratio of radioactivity in the SI joints and in the os sacrum, determined either by a region-of-interest technique or by a profile-scan technique measuring the maxima of the curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the 1980s, SI ratio was being used as important indicator in early vigilance of AS, particularly in males to prevent its progression to sacroiliitis. 49,[54][55][56][57] Although QSS showed a limited sensitivity and specificity of approximately 50% for each when appropriate controls were used, 58,59 the SI ratio of 1.55 meant that AS disease progression was expected to last <3 years and >3 years at 1.40. 60 In 1993, Collie et al 61 measured SI ratios for six of 11 patients (5 female, 6 male), and found elevated ratios (>1.5 for both SI joints) in four of them.…”
Section: Quantitative Sacroiliac Scintigraphy For Spondyloarthropathy Including Ankylosing Spondylitismentioning
confidence: 99%
“…In the 1980s, SI ratio was being used as important indicator in early vigilance of AS, particularly in males to prevent its progression to sacroiliitis. 49,[54][55][56][57] Although QSS showed a limited sensitivity and specificity of approximately 50% for each when appropriate controls were used, 58,59 the SI ratio of 1.55 meant that AS disease progression was expected to last <3 years and >3 years at 1.40. 60 In 1993, Collie et al 61 measured SI ratios for six of 11 patients (5 female, 6 male), and found elevated ratios (>1.5 for both SI joints) in four of them.…”
Section: Quantitative Sacroiliac Scintigraphy For Spondyloarthropathy Including Ankylosing Spondylitismentioning
confidence: 99%
“…The most reliable (Davis et al 1984) is to identify the sacroiliac regions using isocount contours, comparing the ratio of counts per pixel within each of these regions with that of a reference region, usually the upper sacrum (Ho et al 1979;Pfannenstiel et al 1980). It is essential to select a region which is both clear of the bladder and of any arthropathy at the L5/S1 level.…”
Section: Ankylosing Spondylitis and Low Back Painmentioning
confidence: 99%